Transcranial direct current stimulation (tDCS) onthe dorsolateral prefrontal cortex alters P50 gating. (18th August 2015) - Terada, Hidenori; Kurayama, Taichi; Nakazawa, Ken; Matsuzawa, Daisuke; Shimizu, Eiji
Abstract: Transcranial direct current stimulation (tDCS) has been reported to modify cortical function by inducing alterations in the underlying brain function. P50auditory evoked potentials, as assessed using a paired auditory stimulus (S1 and S2) paradigm, are thought to reflect a sensory gating process in which the functional involvement of the dorsolateral prefrontal cortex (DLPFC) is suggested. P50 sensory gating has also been reported to be associated with the pathogenesis of psychiatric diseases such as schizophrenia and anxiety-related disorders. Here we investigated whether the tDCS over the DLPFC could modulate the cortical function leading to alteration of the P50 sensory gating. P50 gating indices (the S2/S1 ratio and S1-S2 difference) were measured during the tDCS (current 1.0 mA, duration 15 min) over the DLPFC with different conditions (anodal, cathodal and sham). Ten male healthy volunteers were studied on separate days in a single blinded paradigm. We observed that the cathodaltDCS significantly altered the mean P50 gating indices compared to the other two conditions. Our results suggest that sensory gating could be modulated by cathodaltDCS on the left DLPFC but not by anodal/sham tDCS.